2021
DOI: 10.2147/dmso.s301068
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV Inhibits Mitochondrial-Dependent Apoptosis of the Dorsal Root Ganglion in Diabetic Peripheral Neuropathy Rats Through Modulation of the SIRT1/p53 Signaling Pathway

Abstract: Purpose To investigate the effect of astragaloside IV (AS-IV) on mitochondrial-dependent apoptosis in the dorsal root ganglion of diabetic peripheral neuropathy (DPN) rats through the SIRT1/p53 pathway. Methods Diabetic rat model was induced by high-carbohydrate/high-fat diet and intraperitoneal injection of STZ. Diabetic rats were divided into three groups (n =16 per group): DPN group, AS-IV group (60mg/kg/d) and α-lipoic acid (ALA) group (60mg/kg/d). Weight and blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 57 publications
(24 reference statements)
1
17
0
Order By: Relevance
“…30 Similar phenomena have also been observed in the dorsal root ganglia of rats with uncle peripheral neuropathy. 18 In the current study, the regulation of SIRT1 and p53 by AS-IV was also observed. After treating STZ pre-incubated INS-1 cells with the SIRT1 inhibitor EX527, the cytoprotective effect of AS-IV was found to be significantly weakened.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…30 Similar phenomena have also been observed in the dorsal root ganglia of rats with uncle peripheral neuropathy. 18 In the current study, the regulation of SIRT1 and p53 by AS-IV was also observed. After treating STZ pre-incubated INS-1 cells with the SIRT1 inhibitor EX527, the cytoprotective effect of AS-IV was found to be significantly weakened.…”
Section: Discussionsupporting
confidence: 65%
“…17 In the process of mitochondrialdependent apoptosis in the dorsal root ganglion of rats with diabetic peripheral neuropathy, it was detected that AS-IV can up-regulate the expression of SIRT1 and inhibit the activation of P53. 18 Resveratrol protects the insulin secretion of INS-1 cells induced by ethanol through the SIRT1/UCP2 axis. 19 Whether the mechanism of AS-IV treatment of diabetes involves the SIRT1 signaling pathway remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study has shown that Drp1 is highly expressed at the spinal cord level [ 33 ]. And many studies have shown different NP contributed to the increased expression of Drp1 [ [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] ]. Here we observed the changes of Drp1 in the SDH of the mice during NP by Western blot and qRT-PCR and also confirmed the increased Drp1 expression ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its complexity of pathogenesis and adverse reactions to drugs, its therapeutic treatment remains a challenge. Among all mechanistic studies, accumulating evidence has pointed to mitochondrial dysfunction [ [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , 45 ]. Neurons are dependent on mitochondria, which not only provide energy to power cellular function through oxidative phosphorylation, but also regulate cellular oxidation-reduction status, calcium levels, signal transduction, and apoptosis [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation